2022
DOI: 10.7717/peerj.14400
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of karyotyping and copy number variation sequencing technology in prenatal diagnosis

Abstract: Background Karyotyping and genome copy number variation sequencing (CNV-seq) are two techniques frequently used in prenatal diagnosis. This study aimed to explore the diagnostic potential of using a combination of these two methods in order to provide a more accurate clinical basis for prenatal diagnosis. Methods We selected 822 pregnant women undergoing amniocentesis and separated them into six groups according to different risk indicators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…But SNP-array showed that there were 68.1Mb duplication in the 9p24.3q13 region and 1.7Mb deletion in 9q34.3 region, which was determined to be pCNVs (Table 2, cases 19). The result showed that compared with standard karyotyping, SNP array could be more informative but it cannot replace karyotyping because of their inability to detect balanced chromosomal translocations or inversions, which consisted with previous reports [18,19].…”
Section: Discussionmentioning
confidence: 62%
“…But SNP-array showed that there were 68.1Mb duplication in the 9p24.3q13 region and 1.7Mb deletion in 9q34.3 region, which was determined to be pCNVs (Table 2, cases 19). The result showed that compared with standard karyotyping, SNP array could be more informative but it cannot replace karyotyping because of their inability to detect balanced chromosomal translocations or inversions, which consisted with previous reports [18,19].…”
Section: Discussionmentioning
confidence: 62%